Analisis Penerapan Ekstrakulikuler Seni Karawitan dalam Membentuk Sikap Cinta Tanah Air pada SD Negeri 5 Karangrowo Undaan Kudus - Ilmi, Alfi Muzaro'atul; Wijayanto, Wasis (FONDATIA, 2024)
This research aims to analyze the application of extracurricular musical arts in forming an attitude of love for the country in students at SD Negeri 5 Karangrowo Undaan Kudus. The research method used is qualitative with a descriptive approach. This research was carried out at SD Negeri 5 Karangrowo Undaan Kudus in March – April 2024. Data was collected through interviews with musical arts teachers, students who took part in musical arts extracurriculars, and students' parents, as well as participatory observation and documentation studies. The data analysis uses include data reduction, data display, and drawing conclusions. The results of the research show that the extracurricular application of musical arts is effective in forming an attitude of love for the country in students, by strengthening cultural identity, forming attitudes of ownership and responsibility, as well as the influence of a positive school and family environment. The conclusion of this research emphasizes the importance of supporting extracurricular musical arts programs as a means of forming an attitude of love for the country in students.